The legal training based on competences: role of skills in the education of the future lawyer - Apaza Jallo, Niels J. (2020)
The paper develops the basic elements that make up competencybased legal training (the role of competencies in law). The perspective of education oriented to train by competencies, or teaching by competencies, implies, in essence, guaranteeing learning through problem solving, involvement in projects, approaching reality and improving the ability to adapt to different environments. This had a great impact on the way students are educated and resulted in the modification of curricula at all levels of education, since competencies are part of education. Furthermore, it gained strength with the accreditation of study programs and the institutional licensing of universities. In this scenario, the purpose of this paper is to give an account of the main characteristics of competency-based education or legal training. And, finally, in a concrete manner, to analyze what the lawyer should know, know and do, within the framework of the knowledge society and the continuous changes that are taking place.